A research agenda for technologically mediated instructional strategies in adult education - Donna L. Kizzier; Ruth S. Lavin (Adult Education Research Conference, 1993)
A research agenda has resulted from a developmental process for studying the effectiveness of technologically mediated instructional strategies.